Human Capital and Environmental Quality in Cameroon - Neba Cletus Yah; Henri Ndame Makembe (Jurnal Ekonomi dan Studi Pembangunan, 2022)
The aim of this paper is to analyze the impact of human capital, notably education, on environmental quality in Cameroon. Used is made of ARDL bound testing techniques to analyze annual data spanning the period 1971-2019. The data was obtained from the World Development Indicators published by the World Bank website. The results show a positive impact of human capital development on environmental quality. Also, evidence was found to support the existence of the environmental Kuznets curve in the context of Cameroon. These results indicate that the government of Cameroon can improve on its environmental quality by developing the human capital of its citizens. This can be done by enhancing environmental education in the country.